Money talks - Marie Hoerova; Cyril Monnet; Ted Temzelides (European Central Bank (ECB), 2009)
We study credible information transmission by a benevolent Central Bank. We consider two possibilities: direct revelation through an announcement, versus indirect information transmission through monetary policy. These two ways of transmitting information have very different consequences. Since the objectives of the Central Bank and those of individual investors are not always aligned, private investors might rationally ignore announcements by the Central Bank. In contrast, information transmission through changes in the interest rate creates a distortion, thus, lending an amount of credibility. This induces the private investors to rationally take into account information revealed through monetary policy.
Keywords: D80; E40; E52; 330; Information; Interest Rates; monetary policy; Geldpolitik; Glaubwürdigkeit; Politische Kommunikation; Zentralbank; Theorie